Prevention of COVID-19 by Strengthening Body’s Immune System through Self-Healing - Cintami Farmawati; Miftahul Ula; Qomariyah Qomariyah (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2020)
Coronavirus Disease 2019 (COVID-19) has infected thousands of people in Indonesia. A strong immune system can ward off COVID-19 transmission. This study aims to determine the prevention of COVID-19 by strengthening the body’s immune system through self- healing. This study uses qualitative methods with analytical descriptive methods. The research subjects were three People in Monitoring (ODP) COVID-19. Based on extensive interviews and observations at the research site as the main tool for data collection, this study produced several findings. First, there are two causes of the decline in the body’s immune system: medical and psychological factors. Medically, the causes of the body’s immune system are weak: lack of exercise, consuming less nutritious food, dehydration, and lack of sleep. Psychological factors, the cause of the body’s immune system is weak due to stress, anger, fear, tension, and emotional. Second, preventing COVID-19 by strengthening the body’s immune system through self-healing, namely self-healing mentally and self-healing physically. Mental self-healing includes relaxation, contemplation, strengthening worship, and happiness. While the physical self-healing includes eating with nutritious and balanced food, maintaining physical fitness, maintaining hygiene, and health. A strong immune system through self-healing can prevent individual from COVID-19. Suggestions for further researchers is that they can broaden the scope of research by examining more deeply, such as variations in research subjects and variable, data analysis.